2016
DOI: 10.1016/j.neuropharm.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Beta-arrestin 2 rather than G protein efficacy determines the anxiolytic-versus antidepressant-like effects of nociceptin/orphanin FQ receptor ligands

Abstract: Background and purpose-Nociceptin/orphanin FQ (N/OFQ) receptor (NOP) agonists produce anxiolytic-like effects in rodents while antagonists promote antidepressant-like effects. The aim of this study was to investigate the effect on anxiety and depression of NOP receptor partial agonists such as the peptides [F/G]N/OFQ(1-13)NH 2 and UFP-113 and the non-peptide AT-090.Experimental approach-In vitro AT-090, UFP-113, and [F/G]N/OFQ(1-13)NH 2 were tested for their ability to promote NOP/G-protein and NOP/β-arrestin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 59 publications
(83 reference statements)
2
34
0
Order By: Relevance
“…In fact several in vivo actions of Ro 64-6198 and Ro 65-6570 were sensitive to NOP antagonists and no longer evident in NOP(−/−) animals (reviewed in Toll et al (2016)). In addition we recently demonstrated that the anxiolytic-like effect of AT-090 in the mouse elevated plus maze can be detected in NOP(+/+) but not NOP(−/−) mice (Asth et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact several in vivo actions of Ro 64-6198 and Ro 65-6570 were sensitive to NOP antagonists and no longer evident in NOP(−/−) animals (reviewed in Toll et al (2016)). In addition we recently demonstrated that the anxiolytic-like effect of AT-090 in the mouse elevated plus maze can be detected in NOP(+/+) but not NOP(−/−) mice (Asth et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Selective NOP antagonists have been investigated as antidepressants (Gavioli and Calo, 2013; Post et al, 2016) and for Parkinson’s disease treatment (Marti et al, 2013, 2004, 2010) whereas selective nonpeptide NOP agonists have shown significant efficacy for anxiety (Gavioli and Calo, 2006; Shoblock, 2007; Witkin et al, 2014) and pain (Schroder et al, 2014; Toll et al, 2016). Recently, NOP receptor partial agonists have also been developed and investigated in models of anxiety and depression (Asth et al, 2016; Ross et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…) and used for characterizing the functional selectivity of novel NOP compounds (Asth et al. ; Bird et al. ; Rizzi et al.…”
Section: Discussionmentioning
confidence: 99%
“…The BRET assay used to investigate the ability of [Dmt 1 ]N/OFQ(1-13)-NH 2 and PWT2-[Dmt 1 ] to promote receptor interaction with G protein and β-arrestin 2 has been previously validated for classical opioid (Molinari et al, 2010) as well as NOP receptors (Malfacini et al, 2015) and then used for characterizing novel ligands (Asth et al, 2016; Bird et al, 2016; Rizzi et al, 2016) or for selecting the best compounds for inducing receptor stability and crystallogenesis (Miller et al, 2015). In line with previous findings (Malfacini et al, 2015; Rizzi et al, 2016), the standard peptides N/OFQ and dermorphin behaved as potent and selective agonists in promoting receptor interaction both with G protein and β-arrestin 2.…”
Section: Discussionmentioning
confidence: 99%